Kepribadian introvert terhadap kemampuan bersosialisasi remaja di sekolah - Meyra Nur Pramesthi; Nourma Ayu Sulistiyowati; Nur Fauziyah (Global Econedu, 2024)
Human communication can be interconnected to convey information, communicate one's wishes, express emotions, and influence others. A form of communication is a form of communication that occurs between people. This form of communication usually takes place in a private setting and includes face-to-face meetings. This internal communication allows us to get to know other people and build relationships with them, but it is also through interpersonal communication that we can solve problems privately. Adler defined personality as a lifestyle or characteristics of a person and how they respond to life's problems, including their goals in life. Introverts prefer to spend time alone, they don't have much energy for social activities. Their energy is quickly drained when in a crowded environment. Having time to be alone recharges my energy. Extroverts don't feel that way. The method used in this research is literature study. The results and discussion of this study show that introverted personality has an impact on children's socialization abilities, especially at the age of teenagers at school.